REVIEW OF THE FACTORS UNDERLYING THE MECHANISMS AND EFFECTS OF ROADS ON VERTEBRATES - Alves da Rosa, Clarissa (Associação Brasileira de Ciência Ecológica e Conservação (ABECO), 2017)
Road ecology is an emerging discipline that attempts to understand the patterns and processes related with road-ecosystem interactions to establish effective mitigation measures of the negative effects of roads on wildlife. Although many advances have been made over the past 10 years, many questions are still unanswered or the information is incomplete. We discussed the factors (characteristics of roads) involved in mechanisms and effects of roads on vertebrates and the knowledge gaps. The factors evaluated were road density, road maintenance involving chemicals, presence of vehicles and traffic volume. We identified five mechanisms resulting from these factors: car avoidance, noise avoidance, road surface avoidance, road attraction and wildlife-vehicle-collisions (WVC). Density of roads causes road surface avoidance, road attraction and WVC; maintenance of roads with chemicals causes noise avoidance, road attraction and WVC; vehicle presence causes noise avoidance, car avoidance and WVC; and traffic volume causes noise avoidance and WVC. WVC was the only mechanism linked to all road factors and it occurs in combination with another mechanism (road attraction); therefore, we believe this to be the mechanism that affects most organisms. We identified many knowledge gaps related primarily to identifying the mechanisms triggered by various factors, especially for tropical organisms. We believe that studies involving tropical species could provide new results due to their greater ecological demands compared with temperate species.